Voluntary drinking and hydration in trained, heat-acclimatized girls exercising in a hot and humid climate - Rivera-Brown, A. M.; Ramirez-Marrero, F. A.; Wilk, B.; Bar-Or, O. (European Journal of Applied Physiology, 2008)
This study examined the effects of beverage composition on the voluntary drinking pattern, body fluid balance and body temperature responses of heat-acclimatized trained girls exercising intermittently in outdoor conditions (WBGT = 30.9 ± 0.2°C). Twelve trained, heat-acclimatized girls (age = 10.6 ± 0.2 years) performed three 3-h sessions, each consisting of four 20-min cycling bouts at 60% VO2max, alternating with 25-min rest. One of three beverages was assigned: unflavored water (W), flavored water (FW) or flavored water plus 6% carbohydrate and 18 mmol/l NaCl (CNa). Drinking was ad libitum. Total intake was similar among conditions (W = 953.3 ± 107.8 ; FW = 1026.5 ± 138.1; CNa = 906.4 ± 107.5 g). A mild hypohydration occurred during the three conditions (W = -1.12%; FW = -0.95%; CNa = -0.74% BW, P > 0.05). Sweat loss, higher than previously reported for sedentary girls, was not different among conditions (W = 1,051.5 ± 90.8; FW = 979.9 ± 72.8; CNa = 1,052.7 ± 52.6 g). The average amount of urine produced (W = 269.8 ± 85.9; FW = 320.8 ± 87.2; CNa = 85.6 ± 9.3 g) was 73 and 68% higher during FW and W, respectively, compared to CNa (CNa vs. FW, P < 0.05). The increase in rectal temperature, heart rate and all perceptual variables did not differ among conditions. In conclusion, flavoring of the water and addition of 6% carbohydrate plus 18 mmol/l NaCl do not prevent mild hypohydration in trained, heat-acclimatized girls with high sweating rates. However, there is a tendency towards a greater fluid retention with the CNa beverage.